2018
DOI: 10.1007/s00268-018-4813-5
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Stereotactic Radiotherapy Using the CyberKnife for Patients with Inoperable Locoregional Recurrences of Differentiated Thyroid Cancer

Abstract: Background Surgical resection is the preferred treatment for locoregional recurrence of differentiated thyroid cancer (DTC). However, some recurrences are unresectable because of their aggressive invasion or severe adhesions. On the other hand, stereotactic radiotherapy (SRT) enables high‐dose irradiation to target lesions, and its usefulness for various cancers has been reported. The objective of the present study was to investigate the feasibility and efficacy of SRT as salvage treatment for locoregional rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…With this system, one can irradiate a target with less damage to proximal organs by moving the robot arm, which has a wide range of motion. With SRT, precise delivery of high-dose radiation to the target can be achieved using a small number of fractions [7]. SRT compared with conventional 3D conformal radiotherapy demonstrated a higher efficacy in tumor control of bone metastases and in limiting radiation to the spinal cord, especially in patients who needed repeat irradiation [3].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…With this system, one can irradiate a target with less damage to proximal organs by moving the robot arm, which has a wide range of motion. With SRT, precise delivery of high-dose radiation to the target can be achieved using a small number of fractions [7]. SRT compared with conventional 3D conformal radiotherapy demonstrated a higher efficacy in tumor control of bone metastases and in limiting radiation to the spinal cord, especially in patients who needed repeat irradiation [3].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, TKIs should be considered for progressive, symptomatic and/or imminently threatening DTC in which satisfactory control using RAI therapy or directed approaches (e.g. surgery, radiation therapy including SRT) is not considered likely [3, 7]. In our view, SRT appears to be a useful preliminary step to TKI treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kawabe et al reported a case of recurrent lymph node metastasis of papillary thyroid carcinoma successfully treated with CyberKnife [7]. Ishigaki et al reported successful SBRT by CyberKnife for 52 locoregional recurrent lesions in 31 patients with recurrent differentiated thyroid cancer [8]. But their cases are mostly papillary carcinoma, and there were only five patients of follicular carcinoma.…”
Section: Discussionmentioning
confidence: 99%